ON THE NEED FOR LONG-TERM CARE AND THE ROLE OF THE STATE IN PROVIDING IT - Dragićević, Marija (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
As societies progress through the processes of industrialization and socioeconomic development, they undergo a demographic transition characterized by increased life expectancy, a growing proportion of elderly individuals within the overall population, and the survival of population subgroups that, in earlier times, often did not reach adulthood. Although the precise effects of prolonged life expectancy on overall health status and the prevalence of disability remain uncertain, and the influence of advancements in medical science and healthcare practices on the quality of life in old age is not easily quantifiable, it is nonetheless clear that increasing longevity inevitably leads to a rising number of individuals requiring some form of long-term care services.            This demand is further exacerbated by an increasing prevalence of chronic illnesses and disabilities not only among the elderly but also within younger age groups, as well as by significant transformations in family structures and caregiving models. The traditional model, based on geographically close family members providing unpaid and direct care, is gradually being replaced by models of care provision that rely on long-distance support and formal caregiving systems. These sociocultural and demographic shifts have significantly reduced the availability of informal caregivers, thereby increasing the pressure on formal care systems and the need for organized and institutional responses.            Despite the uncertainties regarding the complex interplay of demographic aging, shifts in familial roles, and changing health profiles of the population, there is little doubt that contemporary societies are facing a steadily growing need for the establishment, regulation, and maintenance of comprehensive long-term care systems for persons dependent on the help and support of others in their daily lives. In this context, the role of the state becomes crucial—not only in terms of defining public policy priorities and legal frameworks but also in terms of ensuring equitable access, financial sustainability, and the coordination of diverse service providers. This paper discusses the structural determinants of the growing need for long-term care and critically examines the responsibilities of the state in meeting this need, particularly in light of the increasing gap between the demand for care and the available resources—both human and institutional.
Keywords: long-term care; elderly persons; persons with disabilities; demographic change; carers